The Role of the Prosecutor Against the Actors of Narcotics Crime Category 1 in the Binjai District Prosecutor - Surbakti, Benny Avalona; Albisar, Madiasa; Sunarmi, Sunarmi; Mulyadi, Mahmud (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
Cases of narcotics trafficking and abuse in recent years have increased rapidly in big cities in Indonesia, including in Binjai City, where the average users are farmers, drivers, students, and school dropouts. The role of prosecutors as one of the important elements in the criminal justice system occupies a very important role in carrying out their duties and authorities in order to carry out law enforcement, namely prosecution in narcotics crime cases in court, so it is important to conduct research on the role of the prosecutor against the actors of narcotics crime category 1 in the Binjai District Prosecutor. This research is normative and descriptive analysis. The legal theory used in this research is the theory of the criminal justice system, law enforcement, and the purpose of the law. The data used is secondary data which can consist of primary legal materials, secondary legal materials, and tertiary legal materials. The data collection technique is library research. Data analysis is qualitative. The Prosecutor's Office as a subsystem of the criminal justice system contained in the current legislation, both in the Criminal Procedure Code and in the Prosecutor's Law No. 16 of 2004, namely as investigators and public prosecutors. Factors that hinder prosecutors in carrying out law enforcement against perpetrators of narcotics crime group I in Binjai City are the facilities or facilities that support law enforcement. Efforts made by the prosecutor in prosecuting the handling of criminal acts of narcotics abuse Category I at the Binjai City Public Prosecutor's Office that have been carried out so far include holding knowledge sharing meetings between fellow law enforcers, conducting management improvements, conducting legal counseling regarding narcotics crimes. In the general public, continuing education of prosecutors, especially narcotics crimes, and the program for prosecutors to enter schools. This activity is to provide counseling to students regarding the dangers and impacts of narcotics use among school children.